2020
DOI: 10.1631/jzus.b2010010
|View full text |Cite
|
Sign up to set email alerts
|

Possible aerosol transmission of COVID-19 and special precautions in dentistry

Abstract: Since its emergence in December 2019, corona virus disease 2019 (COVID-19) has impacted several countries, affecting more than 90 thousand patients and making it a global public threat. The routes of transmission are direct contact, and droplet and possible aerosol transmissions. Due to the unique nature of dentistry, most dental procedures generate significant amounts of droplets and aerosols, posing potential risks of infection transmission. Understanding the significance of aerosol transmission and its impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
735
0
194

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 604 publications
(936 citation statements)
references
References 35 publications
(32 reference statements)
7
735
0
194
Order By: Relevance
“…A total of 650 participants from 30 countries worldwide submitted the completed questionnaire with a total of 22 questions comprising of two sections about fear or anxiety level and practice modification due to COVID-19. The responses were recorded from various countries as follows: Saudi Arabia (80); Pakistan (200); India (55); United Arab Emirates (45); People's Republic of China (67); Italy (40); United Kingdom (23); Australia (23); Malaysia (22); United States of America (21); Ireland (20); Israel (10); New Zealand (08); South Africa (05); Turkey, Germany, Kuwait, Canada, Hungary, and France recorded (02) each; and Poland, Bulgaria, Republic of the Congo, Mexico, Finland, Romania, Egypt, Switzerland, Demark, and Bahrain recorded (01) each. There were (09) responses from unidentified locations ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 650 participants from 30 countries worldwide submitted the completed questionnaire with a total of 22 questions comprising of two sections about fear or anxiety level and practice modification due to COVID-19. The responses were recorded from various countries as follows: Saudi Arabia (80); Pakistan (200); India (55); United Arab Emirates (45); People's Republic of China (67); Italy (40); United Kingdom (23); Australia (23); Malaysia (22); United States of America (21); Ireland (20); Israel (10); New Zealand (08); South Africa (05); Turkey, Germany, Kuwait, Canada, Hungary, and France recorded (02) each; and Poland, Bulgaria, Republic of the Congo, Mexico, Finland, Romania, Egypt, Switzerland, Demark, and Bahrain recorded (01) each. There were (09) responses from unidentified locations ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Since it has been established that the primary route for transmission of coronavirus is through droplets and aerosols [22], this enhances the likelihood of dentists and dental healthcare workers of getting infected and further spreading the virus. The current study found that a large number of dentists fear getting infected by their patients or co-workers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, acoording recent studies, the aerosol transmission route, the source origin as well as the seasonality of 2019 novel coronavirus are all poorly understood. [37][38][39][40][41][42] Besides, Feng He stated that it is still too early to develop an accurate R 0 estimate or to assess the dynamics of transmission. [43] A better scienti c understanding of the emergence and transmission of the virus in the context of demographic, climate and environmental change is needed in the future, which can help governments make long-term preparation of public health system.…”
Section: Theoretical Reframing Of Urban Health Resources For Better Gmentioning
confidence: 99%